2022
DOI: 10.3390/microorganisms10020482
|View full text |Cite
|
Sign up to set email alerts
|

Organic and Inorganic Amendments Shape Bacterial Indicator Communities That Can, In Turn, Promote Rice Yield

Abstract: The dynamic patterns of the belowground microbial communities and their corresponding metabolic functions, when exposed to various environmental disturbances, are important for the understanding and development of sustainable agricultural systems. In this study, a two-year field experiment with soils subjected to: chemical fertilization (F), mushroom residues (MR), combined application of chemical fertilizers and mushroom residues (MRF), and no-fertilization (CK) was conducted to evaluate the effect of fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Organic fertilization is considered an alternative, more environmentally friendly strategy that can prevent the disadvantages related to the excessive use of chemical fertilization. It has been reported that organic fertilizers could lead to a lower degree of soil nutrition than that of chemical fertilizers [ 5 , 6 ]. Long-term fertilization field experiments in global regions have demonstrated that the simultaneous application of chemical and organic fertilizers is beneficial for modern farming; this is because it can promote crop yield while ensuring soil state and meeting the demand of sustainable and environmentally friendly agriculture [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic fertilization is considered an alternative, more environmentally friendly strategy that can prevent the disadvantages related to the excessive use of chemical fertilization. It has been reported that organic fertilizers could lead to a lower degree of soil nutrition than that of chemical fertilizers [ 5 , 6 ]. Long-term fertilization field experiments in global regions have demonstrated that the simultaneous application of chemical and organic fertilizers is beneficial for modern farming; this is because it can promote crop yield while ensuring soil state and meeting the demand of sustainable and environmentally friendly agriculture [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alongside manure, chemical fertilization is another method to increase plant yields. There are several different types of such fertilizers, and a study by Dr. Qiu and others (“Organic and Inorganic Amendments Shape Bacterial Indicator Communities That Can, In Turn, Promote Rice Yield”) showed how these amendments could both affect microbial community structure and rice yield [ 10 ]. They found that 10 bacterial taxa in the Actinobacteria phyla with roles in xenobiotic metabolism responded strongly to chemical fertilization.…”
mentioning
confidence: 99%